Impugnatorios ordinary means without devolutive: The remedy and appeal for reconsideration - Franciskovic Ingunza, Beatriz (2021)
Through this article we analyze two ordinary means of challenge without devolutive as are the remedy and replacement. Impugnatorios means that our procedural law regulates differentially, considering the reinstatement as a remedy (appeal) and not as a remedy. On the other hand, it listed as a remedy to the opposition, when in the same civil procedure code regulates within evidentiary issues, such as strikeout. This difference relies on the fact that our legal system differentiates remedies based on what what (defects or errors contained or not in a court decision) is questioned and not in its effects (effective or without devolutive).